Extension of analysis interpretive treatise (AIT) package to design capabilities - Chia, Nyan Fatt; Worsak Kanok-Nukulcha; Ogawa, Junji; Ping Kunawatsatit; Australian Government (Bangkok : Asian Institute of Technology, 1981)
The concept of database is employed in the development of AIT (Analysis Interpretive Treatise). Existing capabilities includes: 1) Matrix manipulation and operations: 2) Generation of characteristic arrays of a finite element mesh; 3) Finite element processes, e.g . element stiffness assembling, static condensation, sub structuring, eigenvalue solution. A scheme for implementing the design capability is presented here, and processors for the design of reinforced concrete frame structure are developed. Documentation of modified processors and new processors is given. A three-story building is used to illustrate the design capability of the program.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Structural design -- Data processing